2005
DOI: 10.1039/b507458d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lateral substituents on the mesophase behaviour of banana-shaped mesogens. Part II

Abstract: New materials are presented, derived from the original banana compounds where the first smectic phases with polar switching (SmCP) were detected. Our results demonstrate that the introduction of lateral substituents on the central ring (F, Cl, CN, NO 2 , CH 3 ) and/or on the terminal rings (Cl, Br, CH 3 ) can significantly change the mesophase behaviour. The influence of such substituents is much more pronounced than in comparable calamitic compounds. The clearing temperatures are more or less depressed depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…on BCM have also been investigated. [5,13,26,27,[68][69][70][71][72][73][74] This is of interest because such groups will exaggerate the electrostatic profile (molecular dipole), and computational studies indicate that increasing the transverse dipole might stabilise the biaxial nematic phase (this idea has been investigated experimentally as well). [75][76][77][78] It has been demonstrated that subtle changes in the nature of the lateral groups can alter both the stability and types of liquid crystalline phases observed.…”
Section: Introductionmentioning
confidence: 97%
“…on BCM have also been investigated. [5,13,26,27,[68][69][70][71][72][73][74] This is of interest because such groups will exaggerate the electrostatic profile (molecular dipole), and computational studies indicate that increasing the transverse dipole might stabilise the biaxial nematic phase (this idea has been investigated experimentally as well). [75][76][77][78] It has been demonstrated that subtle changes in the nature of the lateral groups can alter both the stability and types of liquid crystalline phases observed.…”
Section: Introductionmentioning
confidence: 97%
“…Introduction of substituents either in the central unit or in the arms of the BC also has significant effect on the nature of mesophase/s observed. The influence of lateral substituents at the central unit as well as at the outer rings of five-ring resorcinol derivatives [6][7][8] of seven series of compounds clearly demonstrates the effects. In order to examine the influence of larger substituents such as methoxy and ethyl groups, seven-ring compounds containing a biphenyl moiety have also been investigated.…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, novel phases can result, if the central phenyl ring is laterally substituted. Much more information is given in the reviews listed above [5][6][7][9][10][11]. This way, for example, the B 7 phase was at first found for derivatives of 2-nitroresorcinol [12] and the B 5 phase for 2-methylresorcinol esters [13].…”
Section: Introductionmentioning
confidence: 98%